Paraoxonase gene polymorphisms and haplotype analysis in a stroke population - Whalley Lawrence; Cheung John; Cumming Alastair; Ross-Adams Helen; Pasdar Alireza; St Clair David; MacLeod Mary-Joan (BMC, 2006)
Abstract Background Paraoxonase (PON) has anti-atherogenic activity due to its protective function against low density lipoprotein (LDL) oxidation. Alteration of enzyme activity due to polymorphisms in the PON genes may influence the development of atheroma and thus affect stroke risk. Three PON genes (PON1, PON2 and PON3) have been identifiedand mapped to chromosome 7. Methods We looked at the distribution of paraoxonase polymorphisms and haplotype arrangement in 397 Caucasian ischaemic stroke patients and 405 controls. We investigated 6 different common single nucleotide polymorphisms (SNP) in PON genes; two substitutions in PON1 ["A/G": Gln (Q)/Arg (R)] at codon 192 and ["T/A": Leu (L)/Met (M)] at codon 55, two in PON2 at codon 311 ["G/A": Cys (C)/Ser (S)] and codon 148 ["C/G": Ala (A)/Gly (G)] and two SNPs, both "A" to "G" substitutions, in PON3 - intronic rs2074353, which we designated PON3-1 and [Ala (A)/Ala (A)] at codon 99, designated as PON3-3. Dynamic Allele Specific Hybridisation (DASH) was used as the genotyping assay. Haplotype analysis was performed using both PHASE and EHPLUS programs. Results Genotype and allele frequencies were similar in cases and controls. Lipid profiles were not influenced by PON genotype. Haplotype frequencies for the six loci (PON2-148, PON2-311, PON3-3, PON3-1, PON1-55 and PON1-192) were estimated. Comparison of the two programs showed a significant difference in haplotype arrangements with EHPLUS (p-value = 0.005) but not with PHASE Ver.2 (p-value = 0.12). The 112211 (1 = frequent allele, 2 = rare allele) haplotype arrangement was commoner in cases than controls (p = 0.015), and the 111121 haplotype was commoner in controls (p = 0.006). Conclusion Our study did not identify a role for individual paraoxonase gene polymorphisms in the pathogenesis of ischaemic stroke. Findings of haplotype differences should be confirmed in large scale studies. The importance of using a well-validated haplotype analysis program is also underlined.